Kepo di Media Sosial: Studi Psikologi Komunikasi tentang Efek Stalking Digital terhadap Emosi dan Relasi Sosial - Novaldi, Rifki Aditia; Nisaussangadah, Siti; Pratiwi, Rezky Graha (Jurnal Ilmiah Psyche, 2025)
The development of social media has changed the way individuals form social relationships, but has also given rise to the phenomenon of digital stalking the unobtrusive observation of others' lives without direct interaction. This study aims to identify the forms, psychological motives, and impacts of digital stalking behavior in the context of one-way communication. Using a quantitative correlational approach, data were collected from 250 respondents aged 18–35 years through an online questionnaire. The results indicate that the primary motives for stalking behavior are curiosity, the need for connectedness, and self-validation. The intensity of digital stalking is significantly positively correlated with anxiety, envy, and overthinking, and negatively correlated with the quality of social relationships. These findings are supported by a regression model, which shows that psychological motives significantly influence stalking behavior (R² = 0.412). This study confirms that digital stalking is not simply a passive activity, but rather a form of emotionally charged symbolic communication with psychosocial impacts. The main contribution of this study lies in the integration of parasocial, uses and gratifications, and social comparison theories in understanding the dynamics of non-romantic interactions on social media. These results are relevant for the development of psychological interventions and digital literacy strategies.